2020
DOI: 10.3389/fmats.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing and Bioinformatics for Rapidly Identifying Cultural Heritage Spoilage Microorganisms

Abstract: Microbiological methodologies allow understanding the causes that lead to the development of a certain microbial community colonizing an artistic surface, to characterize its composition and describe its role in the deterioration of the constituent materials. Metagenomics allows identifying microbial communities directly in their natural environments, bypassing the need for isolation and cultivation of individual species, thus providing a more comprehensive picture of the biodiversity present on a surface comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…To date, the Nanopore sequencing technology has been scarcely applied in the field of cultural heritage, and only four studies have reported on the advantages of applying this state-of-the-art technology on valuable art objects. Three of these studies (Šoltys et al, 2019;Grottoli et al, 2020;Kisová et al, 2020) reported on the advantages of sequencing long DNA fragments when targeting ribosomal regions. However, all three studies were based on the target amplification approach that avoided inferring the relative proportion of the different phylogenetic groups.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the Nanopore sequencing technology has been scarcely applied in the field of cultural heritage, and only four studies have reported on the advantages of applying this state-of-the-art technology on valuable art objects. Three of these studies (Šoltys et al, 2019;Grottoli et al, 2020;Kisová et al, 2020) reported on the advantages of sequencing long DNA fragments when targeting ribosomal regions. However, all three studies were based on the target amplification approach that avoided inferring the relative proportion of the different phylogenetic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of an appropriate methodology for microbiological research is usually based on conservation restrictions and study purpose, such as general contamination (biodeterioration and human health risk assessment) or targeted research on a given artwork/material [ 19 , 20 , 21 , 22 , 23 ]. For general contamination assessment, the air is the most popular study subject, therefore numerous sampling techniques have been developed with (i) impaction, (ii) filtration, and (iii) impingement as major methods [ 24 ].…”
Section: Inspection Of Methodologies Applied For Identification Anmentioning
confidence: 99%
“…When research on historic surfaces is conducted, only non-invasive or micro-invasive treatment methods can be applied using sterile scalpels, swabs, membrane filters or adhesive tapes [ 22 , 23 , 27 ]. However, it should be noted that the use of various sampling methods can provide different results.…”
Section: Inspection Of Methodologies Applied For Identification Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The practical application of this technology in the field of cultural heritage has been launched in the last two years and is still under development, but the few studies that exist so far on various materials, such as wax, stone, textiles and paintings on canvas-or paper-support, have already reported on the advantages of applying this cutting-edge technology to valuable art objects. Three of these studies, performed on a XVIII Century wax seal ( Soltys et al, 2019), the hypogeum of Basilica di San Nicola in Carcere Church in Rom (Grottoli et al, 2020), and on some XVII Century funeral textile items (Kisov a et al, 2020), have reported on the benefits of sequencing long DNA fragments when dealing with ribosomal regions. In other two studies, the Nanopore sequencing technology was applied for the first time together with a whole genome amplification protocol (WGA), either to make a rapid diagnosis of biological infection in canvas paintings of the XVIII and XIX Century (Piñar et al, 2020b) or to evaluate the complete microbiomes of some emblematic Leonardo da Vinci's drawings (Piñar et al, 2020c).…”
mentioning
confidence: 99%